The Role of Religious Leaders in Strengthening Religious Moderation in Sidomakmur Village - Ilham Prayogi; M. Sayidul Abrori; Irhamudin (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This research is motivated by the importance of strengthening religious moderation in maintaining social harmony amidst diversity. This study aims to analyze the role of religious leaders in strengthening religious moderation in Sidomakmur Village. The study used a qualitative, descriptive approach. Data collection techniques were conducted through interviews, observation, and documentation with research subjects consisting of religious leaders, community leaders, and village residents. The results show that religious leaders have a strategic role as guides, advisors, and role models in instilling the values ​​of religious moderation. The strategies used include persuasive, dialogical, and humanistic preaching approaches through lectures, religious studies, and social interactions. The impact of these roles is seen in increased tolerance, the establishment of social harmony, and conflict resolution through deliberation. However, there are obstacles in the form of the influence of external religious ideologies and the development of social media. Overall, the role of religious leaders is considered effective in maintaining religious moderation and social harmony.